The The Role of the Archipelago Insight in Strengthening Indonesia's Territorial Sovereignty in the Era of Globalization - Nadia, Zahra Nadia Sari; Firdaus, Muhammad Irfansyah; Saputri, Firna Juliana; Anaswa, Kalfika Fidhia; Umam, Rizqi Farikhul (De Cive : Jurnal Penelitian Pendidikan Pancasila dan Kewarganegaraan, 2025)
The Archipelagic Outlook (Wawasan Nusantara) is Indonesia's geopolitical concept that emphasizes territorial unity and national sovereignty. As a national doctrine, this concept not only aims to maintain national unity and integrity but also serves as the foundation for formulating strategic policies related to defense, economy, and socio-culture. This article discusses the implementation of Wawasan Nusantara in various aspects of national life, particularly in the context of Indonesia's territorial sovereignty. Additionally, this study identifies key challenges in implementing this concept and explores strategies to address them. The research employs a literature study with a descriptive-analytical approach to gain a comprehensive understanding of the relevance of Wawasan Nusantara in maintaining national stability. The findings indicate that the implementation of Wawasan Nusantara significantly strengthens national resilience, ensures territorial security, and safeguards the unity of the Unitary State of the Republic of Indonesia (NKRI) amid the continuously evolving global dynamics.